How do UK financial institutions really price their banking products? - Heffernan, Shelagh A. (Journal of Banking & Finance, 2002)
This paper has several objectives. The first is to explore the type (or types) of imperfect competition that prevailed in the retail banking sector in the 1990s. A general linearised pricing model is employed to test for the degree to which competition in certain markets deviated from the competitive ideal. The key finding, is that, with the exception of mortgage products, deposit and loan rate setting by UK financial institutions is best described by the Salop–Stiglitz model of monopolistic competition, with bargain and rip-offs. Cournot type behaviour is evident in some cases. Indirectly, the presence of perfect contestability is largely ruled out. Another objective is to compare these findings with the results of a similar study conducted nearly a decade ago, when financial reforms introduced to encourage greater competition were relatively recent. Based on the results of this study, the policy lesson is that financial firms exhibit different types of price setting behaviour depending on the banking product. The policy implication is to require firms to produce comparable information for consumers, thereby helping to contain the loss of consumer surplus in imperfectly competitive markets.